2020
DOI: 10.22207/jpam.14.4.25
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainability Approach to Treatment of DR-TB Patients through Community Social Organization (Aisyiyah)

Abstract: Multidrug-resistant tuberculosis (MDR-TB) is currently an important public health problem in the world. Treatment of MDR-TB patients takes a long time, 20-24 months in standard regimen or 9-11 months in shorter regimen. Long treatment duration and drug toxicities which higher than drug-sensitive TB can cause drop out of treatment. Aisyiyah is a community social organization which provide assistance to TB patients in order to complete the treatment within specified time period. This study aimed to compare the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Community DOT clients were also likely to achieve a cured outcome. This finding is consistent with the results of previous systematic reviews and meta -analyses [22] , [23] , [24] and other studies in Indonesia [25] and South Africa [26] where CBDOT was reported to improve treatment cure and reduce the mortality rate. One plausible reason is that in CBDOT, patients with tuberculosis take medications under the direct supervision of a treatment supporter at home or in their community, allow family support, and eliminate long and costly trips to a centralized primary health facility.…”
Section: Discussionsupporting
confidence: 93%
“…Community DOT clients were also likely to achieve a cured outcome. This finding is consistent with the results of previous systematic reviews and meta -analyses [22] , [23] , [24] and other studies in Indonesia [25] and South Africa [26] where CBDOT was reported to improve treatment cure and reduce the mortality rate. One plausible reason is that in CBDOT, patients with tuberculosis take medications under the direct supervision of a treatment supporter at home or in their community, allow family support, and eliminate long and costly trips to a centralized primary health facility.…”
Section: Discussionsupporting
confidence: 93%